Chondrolipoma of the stomach. Issue 3 (15th March 2019) - Chen, Reuben J; Sun, Yi Qiu; Hii, Michael W; Johnson, Mary Ann
Abstract : Chondrolipoma, a rare variant of a lipoma, is a benign mesenchymal neoplasm characterised by mature adipocytes with neoplastic hyaline cartilage formation. We describe the first case of a gastric chondrolipoma. The tumour was completely excised via laparoscopic gastric wedge resection with uneventful postoperative recovery. Histology of the tumour demonstrates mature adipose tissue and benign cartilage with patchy calcification.